Männer in Österreichs Kinderbetreuungseinrichtungen Impulse für eine "geschlechtsneutrale" Professionalität in der Elementarpädagogik - Koch, Bernhard (innsbruck university press, 2012)
The low representation of men in elementary educational institutions is now largely understood as a problem by educational science but also by politics, the media and parents. The intention of the book is to make men in education visible and to provide impulses for a "gender neutral" professionalism in elementary education. This volume contains the dissertation written by the author as part of a research project funded by the FWF Science Fund at the University of Innsbruck. After an introductory section on the history of the kindergarten, career choices and the importance of men in child care, empirical results from research are presented and discussed in three main groups: young people prior to career choices, young men and women in education and active educators. The extensive evaluations of the questionnaire surveys and the detailed interview statements give a very "plastic" and varied picture of men in kindergarten. For the first time compressed statements of men and women in child care are compared and made available to the public. The results show the profile and the experiences of men as well as their way into the profession. Represented and analyzed are similarities and differences in the sexes. The book concludes with considerations on how to increase the proportion of men in early education.